Is Promotion of Mobility in Older Patients Hospitalized for Medical Illness a Physician’s Job?—An Interview Study with Physicians in Denmark - Mette Merete Pedersen; Rasmus Brødsgaard; Per Nilsen; Jeanette Wassar Kirk (Geriatrics, 2020)
The aim of this study was to identify the most common barriers and facilitators physicians perceive regarding their role in the promotion of mobility in older adults hospitalized for medical illness as part of on an intervention to promote mobility. Twelve physicians at two medical departments were interviewed face-to-face using semi-structed interviews based on the Theoretical Domains Framework. The physicians’ perceived barriers to promoting mobility were: the patients being too ill, the department’s interior does not fit with mobility, a culture of bedrest, mobility not being part their job, lack of time and resources and unwillingness to accept an extra workload. The facilitators for encouraging mobility were enhanced cross-professional cooperation focusing on mobility, physician encouragement of mobility and patient independence in e.g., picking up beverages and clothes. The identified barriers and facilitators reflected both individual and social influences on physicians’ behaviors to achieve increased mobility in hospitalized older medical patients and suggest that targeting multiple levels is necessary to influence physicians’ propensity to promote mobility.